Levator Ani Muscle Trauma during Childbirth and Its Relationship with Postpartum Depression - Tahir, Ayesha; Imtiaz Afzal, Hafiz Muhammad; Faisal, Sanober; Shahzad, Naeem; Afzal, Sidra; Khan, Ayaz Muhammad (Journal of Neonatal Surgery, 2025)
Objective: To determine the prevalence of levator ani muscle (LAM) trauma during vaginal delivery and examine its association with postpartum depression (PPD) among Pakistani women. Design: Prospective multicentre cohort study. Setting: Tertiary care hospitals in Pakistan from July, 2024 to June 2025. Participants: Five hundred women aged 18–40 years with singleton vaginal deliveries were enrolled. Exclusion criteria included prior psychiatric illness, cesarean delivery, multiple gestation, or major obstetric complications. Main Outcome Measures: LAM trauma was assessed within 48 hours postpartum using transperineal ultrasonography. PPD was evaluated at six weeks using the Edinburgh Postnatal Depression Scale (EPDS), with scores ≥13 indicating probable depression. Obstetric and demographic data were collected, and multivariate logistic regression was used to evaluate associations. Results: LAM trauma was detected in 34% of participants. PPD was present in 22% of women, with a significantly higher prevalence among those with LAM trauma compared to those without (35% vs 15%, p<0.001). Women with LAM trauma had more than twice the odds of developing PPD (adjusted OR 2.1, 95% CI 1.4–3.2) after adjusting for age, parity, mode of delivery, and birth weight. Instrumental delivery, prolonged second stage of labor, and birth weight >3.5 kg were independent predictors of LAM trauma. Conclusions: Levator ani muscle trauma is common after vaginal delivery in Pakistani women and is independently associated with postpartum depression. Early identification of pelvic floor injury and integration of mental health support into postpartum care may improve maternal outcomes and reduce the burden of postpartum depression..